Posterior Variant of Alien Limb Syndrome with Sudden Clinical Onset as Self-Hitting Associated with Thalamic Stroke - Mirella Russo; Claudia Carrarini; Fedele Dono; Vincenzo Di Stefano; Maria Vittoria De Angelis; Marco Onofrj; Stefano L. Sensi (Case Reports in Neurology, 2020)
We present a case of sudden postischaemic onset of alien limb syndrome, with unintentional self-injury. Alien limb syndrome is an uncommon neurological disorder featured by uncontrolled and involuntary movements of a limb. Three variants of alien limb syndrome have been described: the anterior, featured by grasping of surrounding objects, the callosal, presenting with intermanual conflict, and the posterior, associated with involuntary levitation of the limb. Our patient suffered from an acute presentation of the posterior variant of the alien limb syndrome, resulting from an isolated thalamic stroke which was documented using 24-h computed tomography brain scan. Only one previous case of alien limb syndrome after thalamic infarct has been reported. Our case enhances the possibility that pure thalamic injury may represent a trigger for this condition.